PERJANJIAN PERKAWINAN; ASAS KESEIMBANGAN DALAM PERKAWINAN - Kurniawan, Puji (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
A marriage agreement is an agreement between a prospective husband and wife to regulate matters that are mutually agreed upon especially regarding assets in their marriage, provided that they do not conflict with law, decency and public order, and pay attention to general rules relating to the prohibition of the contents of the marriage agreement. This is in accordance with the principle of balance that we can find in the legislation.